2019
DOI: 10.1002/ajmg.c.31749
|View full text |Cite
|
Sign up to set email alerts
|

The CHD8 overgrowth syndrome: A detailed evaluation of an emerging overgrowth phenotype in 27 patients

Abstract: CHD8 has been reported as an autism susceptibility/intellectual disability gene but emerging evidence suggests that it additionally causes an overgrowth phenotype. This study reports 27 unrelated patients with pathogenic or likely pathogenic CHD8 variants (25 null variants, two missense variants) and a male:female ratio of 21:6 (3.5:1, p < .01). All patients presented with intellectual disability, with 85% in the mild or moderate range, and 85% had a height and/or head circumference ≥2 standard deviations a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 21 publications
1
44
0
Order By: Relevance
“…Behavioral abnormalities in the open-field test worsen with age in Chd8 V986*/+ mice ASD disproportionally affects males over females (~4:1), ASD-linked mutations in CHD8 are more common in males (3.5:1) [13] and only Chd8 mutant male mice (with a different heterozygous loss-of-function allele, Asn2371LysfsX2; shown in Fig. 1) had behavioral abnormalities [20].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Behavioral abnormalities in the open-field test worsen with age in Chd8 V986*/+ mice ASD disproportionally affects males over females (~4:1), ASD-linked mutations in CHD8 are more common in males (3.5:1) [13] and only Chd8 mutant male mice (with a different heterozygous loss-of-function allele, Asn2371LysfsX2; shown in Fig. 1) had behavioral abnormalities [20].…”
Section: Resultsmentioning
confidence: 99%
“…Subsequent studies found that de novo heterozygous loss-of-function mutations in CHD8 are relatively common in ASD probands [4,[8][9][10][11][12]. Individuals with disruptive CHD8 mutations are disproportionately male (3.5:1) and present with shared symptoms, including macrocephaly, neonatal hypotonia, distinct facial features, and gastrointestinal problems [9,13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CHD8, connecting BAF and COMPASS complexes, negatively regulates β-catenin-targeted gene expression important in cellular proliferation and differentiation ( 55 , 56 ). In Chd8 depleted mice, PRC2 regulation of WNT signaling appears to be the major altered pathway ( 57 ), and accordingly, an overgrowth phenotype with macrocephaly has been reported in CHD8-related NDD patients and animal models ( 28 , 58–60 ).…”
Section: Transcriptional Convergence In Neurogenesis: Wnt Signalingmentioning
confidence: 99%
“…In addition to ASD, CHD8 has been associated with other clinical features, such as macrocephaly, gastrointestinal problems, regression of acquired skills, intellectual disability, some recurring facial features, and seizures. The gene encodes for the chromatin remodeling factor CHD8, which is a member of the chromodomain‐helicase‐DNA binding proteins, involved in chromatin dynamics, transcriptional regulation, and cell survival 46–50 …”
Section: The Epileptic Phenotype Of Candidate Genesmentioning
confidence: 99%